Integrating the Prevention and Control of Rheumatic Heart Disease into Country Health Systems: A Systematic Review and Meta-Analysis. Issue 1 (14th September 2020) - Abrams, Jessica; Watkins, David A.; Abdullahi, Leila H.; Zühlke, Liesl J.; Engel, Mark E.
Background: National and international political commitments have been made recently on rheumatic heart disease (RHD), a preventable heart condition that is endemic in low-resource countries. To inform best practice and identify evidence gaps, we assessed the effectiveness of RHD prevention and control programmes and the extent and nature of their integration into local health systems. Methods: We conducted a systematic review and meta-analysis using a previously published protocol that included electronic and manual searches for studies published between January 1990 and July 2019 reporting on prevention and control programmes for populations at risk for streptococcal pharyngitis, rheumatic fever, and/or RHD. We analysed programme integration according to a previously published framework and programme effectiveness using a results-chain framework. We meta-analysed secondary prophylaxis adherence using random-effects models. Study quality was assessed using peer-reviewed checklists (CASP and PRISM). PROSPERO registration: CRD42017076307. Findings: Five observational studies met with the inclusion criteria. Studies were similar in extent and nature of integration into health systems; no programme was completely integrated or non-integrated. A single study reported on programme impact. Secondary prophylaxis adherence improved among partially integrated RHD programmes (RR, 1.18 [95% CI, 1.03 to 1.36], 3 studies, n = 618). Risk of bias was low in two studies, and indeterminable in the remaining three studies. Interpretation: There is evidence that partially integrated RHD programmes are beneficial for a range of intermediate health outcomes. This review provides a starting point for the design and implementation of future RHD programmes by outlining current best practice for integration and identifying key gaps in knowledge. Funding: National Research Foundation of South Africa.